The Legal Authority of Clemency in Mitigating Sentences for Convicts in Planned Murder Cases - Budhi Mahayana, I Gede; Bagiastra, I Nyoman (Riviera Publishing, 2023)
Planned murder is a regular form of homicide, similar to Article 338 of the Indonesian Criminal Code (KUHP), but it is carried out with premeditation. Notable cases of planned murder in Indonesia include the 'kopi siandia' case, which resulted in the death of Mirna, and the planned murder case of Brigadier J by Ferdy Sambo. The president can grant clemency upon the convict's request, taking into account the considerations of the Supreme Court. Clemency can be seen as a form of presidential pardon after the convict submits a request to the President. The aim of this research is to analyze the legal strength of clemency in mitigating sentences for convicts in cases of planned murder. This study is a normative legal research employing legislative and historical approaches. Primary and secondary legal materials are used as sources, utilizing qualitative descriptive analysis method. Convicts involved in planned murder cases who request clemency from the president may have their sentences mitigated by the court, either through leniency, a change in the type of punishment, reduction of the punishment, or the abolition of the punishment execution. This clemency is an acknowledgment from the convict, admitting to their actions based on the facts. Consequently, the president will consider whether to grant or deny the clemency request based on this admission, considering the Supreme Court's recommendations. Clemency serves as a legal recourse for convicts to lighten or modify their sentences.